2017
DOI: 10.2196/resprot.7523
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Parental Uncertainty Around Childhood Cancer: Implementation Decisions and Design Trade-Offs in Developing an Electronic Health Record-Linked Mobile App

Abstract: BackgroundParents of children newly diagnosed with cancer are confronted with multiple stressors that place them at risk for significant psychological distress. One strategy that has been shown to help reduce uncertainty is the provision of basic information; however, families of newly diagnosed cancer patients are often bombarded with educational material. Technology has the potential to help families manage their informational needs and move towards normalization.ObjectiveThe aim of this study was to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…This strategy has been similarly used in other apps to successfully gauge end-user needs early in the project. 19,37,38 We also found that engagement of both parents and clinicians in the alpha and beta testing phases provided critical feedback for app design. Parents indicated a strong preference for displaying emergency contact information on the app's "home" screen, moving navigation buttons to the bottom of the screen, and developing a one-touch dialing function that would allow parents to quickly place a call in an urgent situation.…”
Section: Proportion Of Interviews Details From Interviewsmentioning
confidence: 77%
See 1 more Smart Citation
“…This strategy has been similarly used in other apps to successfully gauge end-user needs early in the project. 19,37,38 We also found that engagement of both parents and clinicians in the alpha and beta testing phases provided critical feedback for app design. Parents indicated a strong preference for displaying emergency contact information on the app's "home" screen, moving navigation buttons to the bottom of the screen, and developing a one-touch dialing function that would allow parents to quickly place a call in an urgent situation.…”
Section: Proportion Of Interviews Details From Interviewsmentioning
confidence: 77%
“…We found that engaging a SAB that included both parents and clinicians resulted in valuable feedback during the design phase, and led to early design changes (e.g., addition of journaling and appointment tracking features) instrumental in increasing user engagement. This strategy has been similarly used in other apps to successfully gauge end‐user needs early in the project 19,37,38 …”
Section: Discussionmentioning
confidence: 99%